First-in-Human Implantation of Gutter-Free Design Stent-Graft in in situ Fenestration TEVAR for Aortic Arch Pathology - Li, Xin; Shu, Chang; Wang, Lunchang; Li, Quanming; Fang, Kun; Luo, Mingyao; Zhang, Weichang; Zhou, Yang; Zhou, Haiyang (Frontiers in Cardiovascular Medicine, 2022)
Purpose To report the technology and preliminary result of gutter-free design stent-grafted in in situ fenestration thoracic endovascular aortic repair (TEVAR). Description The gutter-free stent-graft has a nickel-titanium self-expanding skeleton, double polytetrafluoroethylene coating, and an outer-skirt fabric structure (named C-skirt endograft). The outer skirt fabric prevents endoleak from the gutter around the stent graft fenestration. Further, the skirt structure right under the fenestration in the aortic stent graft can function as a fixation of the side-branch artery endograft. These designs have the following advantages, such as: 1) prevention of endoleak; and 2) fixation tightly between the branch and aorta endograft pieces. Evaluation A patient who was diagnosed with an aortic arch aneurysm, combined with localized dissection, has successfully implanted the aortic stent graft and C-skirt endograft for the left subclavian artery. The 6-month follow-up result of the C-skirt in situ fenestration TEVAR is satisfactory without obvious endoleak. Conclusions The new gutter-free C-skirt stent graft is being safely and effectively used for aortic arch TEVAR. Long-term evaluation of safety, effectivity, and durability needs to be proven by future multi-center studies.